Proceedings of the 52nd Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2014
DOI: 10.3115/v1/p14-1101
|View full text |Cite
|
Sign up to set email alerts
|

Weak semantic context helps phonetic learning in a model of infant language acquisition

Abstract: Learning phonetic categories is one of the first steps to learning a language, yet is hard to do using only distributional phonetic information. Semantics could potentially be useful, since words with different meanings have distinct phonetics, but it is unclear how many word meanings are known to infants learning phonetic categories. We show that attending to a weaker source of semantics, in the form of a distribution over topics in the current context, can lead to improvements in phonetic category learning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The results showed that information from the derived lexicon and semantics, albeit very rudimentary, help discriminate between allophonic and phonemic contrasts, with a high degree of accuracy. Thus, this works strongly support the claim that the lexicon and semantics play a role in the refinement of the phonemic inventory (Feldman et al, 2013a;Frank et al, 2014), and, interestingly, that this role remains functional under more realistic assumptions (unsupervised word segmentation, and bottom-up inferred semantics). We also found that lexical and semantic information were not redundant and could be usefully combined, the former being more resistant to the scarcity of data and variation, and the latter being more resistant to segmentation errors.…”
Section: General Discussion and Future Worksupporting
confidence: 82%
“…The results showed that information from the derived lexicon and semantics, albeit very rudimentary, help discriminate between allophonic and phonemic contrasts, with a high degree of accuracy. Thus, this works strongly support the claim that the lexicon and semantics play a role in the refinement of the phonemic inventory (Feldman et al, 2013a;Frank et al, 2014), and, interestingly, that this role remains functional under more realistic assumptions (unsupervised word segmentation, and bottom-up inferred semantics). We also found that lexical and semantic information were not redundant and could be usefully combined, the former being more resistant to the scarcity of data and variation, and the latter being more resistant to segmentation errors.…”
Section: General Discussion and Future Worksupporting
confidence: 82%
“…Initial modeling work investigating the feasibility of learning phonetic categories through distributional learning sidestepped the lack of invariance and phonetic category segmentation problems by focusing on drastically simplified learning conditions (40)(41)(42)(43)(44)(45), but subsequent studies considering more realistic variability have failed to learn phonetic categories accurately (9,12,14,15,46,47) (see Supplementary Discussion 1).…”
Section: R a F Tmentioning
confidence: 99%
“…the degree of vocal tract opening at a constriction-and some accounts remain noncommittal (7). natural speech (9,12,14,15,43,(46)(47)(48). Attempts to extend 101 them to more realistic learning conditions have failed (13,16) 102 (see Supplementary Discussion 1).…”
Section: R a F Tmentioning
confidence: 99%
“…Notice that this distribution needs to be defined over an infinite set of possible expansions, since the learner does not know ahead of time which expansions will be needed for their language. Recent probabilistic models of language acquisition , 2010Feldman, Griffiths, Goldwater, & Morgan, 2013;S. Frank, Feldman, & Goldwater, 2014;Goldwater et al, 2009), have demonstrated that Dirichlet Processes can be used to successfully model such infinite distributions, so we adopt that approach here.…”
Section: The Probabilistic Modelmentioning
confidence: 99%